2013 IEEE 7th International Conference on Self-Adaptive and Self-Organizing Systems 2013
DOI: 10.1109/saso.2013.10
|View full text |Cite
|
Sign up to set email alerts
|

A Reductionist Approach to Hypothesis-Catching for the Analysis of Self-Organizing Decision-Making Systems

Abstract: A difficulty in analyzing self-organizing decision-making systems is their high dimensionality which needs to be reduced to allow for deep insights. Following the hypothesis that such a dimensionality reduction can only be usefully determined in an act of a low-scale scientific discovery, a recipe for a data-driven, iterative process for determining, testing, and refining hypotheses about how the system operates is presented. This recipe relies on the definition of Markov chains and their analysis based on an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 27 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…In experiments, the complexity of the collective motion is reduced to a pseudo-1-d setting by using a ring-shaped arena. Microscopic [Czirók et al, 1999] and macroscopic models [Yates et al, 2009, Hamann, 2012, 2013b of this behavior have been reported. Here we use the microscopic model of self-propelled particles by Czirók et al [1999] as our reference model (henceforth 'Czirók model').…”
Section: Locust Scenariomentioning
confidence: 93%
See 3 more Smart Citations
“…In experiments, the complexity of the collective motion is reduced to a pseudo-1-d setting by using a ring-shaped arena. Microscopic [Czirók et al, 1999] and macroscopic models [Yates et al, 2009, Hamann, 2012, 2013b of this behavior have been reported. Here we use the microscopic model of self-propelled particles by Czirók et al [1999] as our reference model (henceforth 'Czirók model').…”
Section: Locust Scenariomentioning
confidence: 93%
“…In the locust scenario, the first priority for the swarm is to achieve alignment which is generally independent of agents' positions. However, locusts seem to depend heavily on spatial features such as the number of neighbors [Hamann, 2013b]. In the following, we briefly investigate the difference between well-mixed systems and systems whose agents' spatial distributions are biased by agents' headings.…”
Section: Well-mixed and Biased Spatial Distributionsmentioning
confidence: 99%
See 2 more Smart Citations